Matched Primary and Locally Recurrent Breast Tumors Distances at the Copy Number, RNA, and Protein levels - de Marchi, Tommaso (Lund University, 2023)
Copy number, RNA reads, and protein intensities -based inter-sample distance. "CN.distance" reports Cosine copy number-based pairwise distances between paired primary and locally recurrent breast cancers. "RNA.DISTANCE" and "PROTEIN.DISTANCE" reports RNA- and PROTEIN-based distance between the paired samples (as above).

Distance was calculated with the following:

1 - Cosine similarity

This dataset was used for Figure 4 in the following manuscript:

"Proteogenomics decodes the evolution of human ipsilateral breast cancer". De Marchi T, Pyl PT, Sjöström M, Reinsbach SE, DiLorenzo S, Nystedt B, Tran L, Pekar G, Wärnberg F, Fredriksson I, Malmström P, Fernö M, Malmström L, Malmström J, Nimèus E. accepted for publication
Keywords: Genomics and transcriptomics; Proteomics and metabolomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik